Tobias Anton Seeman und seine Kalendereinträgen aus den Jahren 1726–1747 - Kubeš, Jiří; Prchal, Vítězslav (Theatrum historiae, 2012)
The article deals with the daily calendar entries of Tobias Anton Seeman from the second quarter of 18 century. Seeman served as the Hofmeister to Bohemian noble Franz Anton Count Sporck and then to his successor Franz Karl Count Swéerts-Sporck. Majority of these entries are preserved in original calendars (17 years), three calenders were lost and they are known in the modern transcriptions from the beginning of 20 century only. The authors introduce the project that was solved at the University of Pardubice (2009–2011) and in its frame the Seeman ́s calendar entries are going to be published in the form of a modern critical bilingual edition during 2012. Finally, the article brings a short biography of Tobias Anton Seeman who was serving to his above mentioned masters for long 60 years.